Dynamics research of Fangzhu's nanoscale surface. Issue 2 (June 2022) - Wu, Pinxia; Ling, Weiwei; Li, Xiumei; He, Xichun; Xie, Liangjin
In this paper, we mainly focus on a fractal model of Fangzhu's nanoscale surface for water collection which is established through He's fractal derivative. Based on the fractal two-scale transform method, the approximate analytical solutions are obtained by the energy balance method and He's frequency–amplitude formulation method with average residuals. Some specific numerical experiments of the model show that these two methods are simple and effective and can be adopted to other nonlinear fractal oscillators. In addition, these properties of the obtained solution reveal how to enhance the collection rate of Fangzhu by adjusting the smoothness of its surfaces.